Understanding The Factors that Decrease Football Athlete's Performances - Sriningsih; Aditya Rajasa; Akhmad Olih Solihin (Journal of Physical and Outdoor Education, 2026)
Performance is the ability or result of work in doing something or an activity task. This study aims to understand the performance factors of soccer athletes, this study was conducted in Cimahi City, North Cimahi, West Java. This study uses a narrative qualitative method. Based on the results of open interviews conducted with respondents. Interviews conducted by the author in May are one of the data collection methods for this study. The author conducted interviews with several respondents who have insight and experience related to soccer, with the aim of obtaining more detailed information about the decline in soccer athlete performance. Based on the results of the study, it shows that the performance of soccer athletes is influenced by factors such as physical (endurance, muscle strength, routine training), technique and tactics (coach instructions and personal initiative), mentality (personal rituals for focus and confidence), as well as field conditions and match atmosphere that have an impact on the game and player psychology.